"Job seeker" experiences of punitive activation in Job Services Australia. Issue 4 (17th November 2020) - Casey, Simone
Abstract: The Job Services Australia era (2009–2015) was a distinct stage in the evolution of Australia's employment services because it was then that "work‐first" payment by results contracts, in combination with demanding "work‐first" activation, resulted in "punitive activation". Experiences of this shift were collected in interviews with a small cohort of job seekers about incidents involving threat of sanction. These incidents involving threat of sanction were construed as moments where job seekers were directly exposed to the coercive authority of activation workers deployed to meet "work‐first" targets. The findings show that "work‐first" marketisation incentives combined with demanding "work‐first" activation led to an experience of "punitive activation".